A block copolymer modified para-aramid polymer solution and its preparation method and application
By introducing a flexible third monomer into the para-aramid for block copolymerization, the problem of easy out-of-control of the existing para-aramid polymerization process is solved, and the heat shrinkage performance and puncture strength of the lithium battery separator are improved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411657473.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing polymerization process of para-aramid is easily out of control and unstable polymerization, resulting in unstable heat shrinkage performance and insufficient puncture strength in lithium battery separators.
The preparation method of block copolymerization modified para-aramid polymerization liquid is adopted, and the introduction of flexible third monomers for standard block copolymerization is improved, the solubility and stability of the polymer are controlled, and the polymerization degree is obtained to obtain a polymerization liquid with excellent performance.
The stability and fluidity of the polymer liquid are improved, and a modified aramid coated separator with excellent heat shrinkage performance, high film rupture temperature, porous structure and high puncture resistance are obtained, which is suitable for the industrial production of lithium battery separators.
Smart Images

Figure CN119161572B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a block copolymerization modified para-aramid polymer solution and a preparation method and application thereof, belonging to the technical field of polymer materials. Background Art
[0002] Aromatic polyamide is mainly based on poly(p-phenylene terephthalamide), which is called para-aramid (PPTA) in China, also known as aramid 1414. It is a rigid liquid crystal polymer material with excellent chemical stability and thermal stability. Its fiber has excellent mechanical properties of high strength and high modulus, and also has excellent physical and chemical properties such as high temperature resistance, flame retardancy, low density, and corrosion resistance. It is widely used in defense, military industry, aerospace, automotive industry and other fields. Para-aramid has a rigid chain structure, and there is a strong hydrogen bond between molecular chains. Its melting temperature is higher than the decomposition temperature, and it is difficult to dissolve in ordinary solvents. It can only be dissolved in strong acids such as concentrated sulfuric acid, which limits the application of para-aramid.
[0003] In order to improve the solubility of para-aramid, a third monomer is usually introduced for co-condensation. The addition of the third monomer can improve the rigid structure of the main chain of the molecule, achieve the effect of destroying the molecular regularity, and improve the solubility of the polymer in ordinary solvents. In general, the co-condensation of para-aramid is to dissolve the aromatic diamine and the third monomer in an organic solvent, and then add terephthaloyl chloride step by step for low-temperature polycondensation. However, this polymerization method is easily affected by many factors such as monomer reactivity, oxidation of aromatic diamines, and hydrolysis of acyl chloride, resulting in the polymerization reaction being easy to lose control and unstable polymerization.
[0004] In recent years, para-aramid has been applied to the field of lithium battery separators due to its excellent thermal and mechanical stability. Chinese patent application CN110729437A uses copolymerization to introduce flexible monomers into the para-aramid molecular chain, and obtains a para-aramid lithium battery separator with high porosity and uniform structure by freeze drying or heat drying. However, the thickness of this separator is not easy to control and the heat shrinkage performance is unstable, which leads to difficulties in actual lithium battery applications. Chinese patent application CN107170942A coats aramid on the surface of a polyolefin base film to obtain an aramid coating, and obtains an aramid composite separator by a non-solvent induced phase transition method, but there are difficulties in interface composite, and the problem of adding additives such as binders is required. Chinese patent application CN104993089A dissolves aramid fibers to obtain a coating slurry and then coats aramid, which leads to unfavorable factors such as degradation of aramid during the dissolution process, affecting the performance of the aramid separator.
[0005] Para-aramid is a rigid polymer with a logarithmic viscosity of 5-8 dL / g, high brittleness, low elongation, and difficulty in forming a uniform and stable film. Direct application in the field of lithium battery separators has disadvantages and is prone to puncture and other safety hazards. Therefore, improving the polymerization process of para-aramid and introducing flexible monomers for block copolymerization can effectively improve the stability of the polymer solution and improve thermal properties, which is of great significance for the preparation of lithium battery separators with excellent heat shrinkage properties and high safety performance. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a block copolymer modified para-aramid polymer solution and a preparation method and application thereof. Through a regular block copolymerization method, a third monomer is regularly introduced into the para-aramid molecular chain as a flexible unit to improve the solubility of the polymer, enhance the stability of the polymer solution, effectively control the degree of polymerization, and obtain a polymer solution with excellent performance. The polymer solution is applied to the field of lithium battery separators to obtain a modified aramid coated separator with excellent heat shrinkage performance, high film rupture temperature, porous structure, and high puncture resistance.
[0007] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a block copolymer modified para-aramid polymer solution, the preparation method comprising:
[0008] S1. Preparation of polymerization solution:
[0009] Under an inert gas atmosphere, dissolving a solubilizing salt in an organic solvent to obtain the polymerization solution;
[0010] S2, precondensation:
[0011] Adding a third monomer and terephthaloyl chloride to the polymerization solution, controlling the reaction temperature to perform a pre-polycondensation reaction, and obtaining an amino-terminated oligomer system, wherein the third monomer is any one of 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 4,4'-diaminobiphenyl, and 4,4'-diaminodiphenylmethane;
[0012] S3, block copolymerization:
[0013] Adding p-phenylenediamine and terephthaloyl chloride to the oligomer system, and controlling the stirring reaction temperature to carry out block copolymerization reaction under stirring conditions;
[0014] S4, Neutralization treatment:
[0015] After the block copolymerization reaction is completed, a neutralizing agent is added to neutralize the acidic substances generated during the reaction, and finally a modified para-aramid polymerization solution in a neutral environment is obtained.
[0016] Further, the organic solvent is at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N,N'-dimethylacetamide, N,N'-dimethylacetamide, and 1,2-dimethyl-2-imidazolidinone;
[0017] The water content of the organic solvent is lower than 150 ppm.
[0018] Furthermore, the dissolution-aiding salt is any one of calcium chloride and lithium chloride, and the mass concentration of the dissolution-aiding salt in the polymerization solution is 0.5% to 6%.
[0019] Further, in step S2, the molar ratio of the third monomer to terephthaloyl chloride is (1.05-1.2):1;
[0020] In step S3, the molar ratio of p-phenylenediamine to terephthaloyl chloride is (0.75-0.9):1;
[0021] The feeding amount of terephthaloyl chloride in step S2 accounts for 55% to 65% of the total feeding amount of terephthaloyl chloride in steps S2 and S3.
[0022] Furthermore, the reaction temperature of step S2 is -5°C to 10°C; the reaction temperature of step S3 is -5°C to 10°C.
[0023] Furthermore, in step S4, the neutralizing agent is any one of calcium oxide, calcium hydroxide, calcium carbonate, lithium carbonate, and lithium hydroxide.
[0024] Furthermore, in step S1, the temperature condition for preparing the polymerization solution is 60°C to 120°C;
[0025] In step S4, the temperature condition of the neutralization treatment is 70-100°C.
[0026] The invention also discloses a block copolymer modified para-aramid polymer solution, wherein the modified para-aramid polymer solution is prepared according to the preparation method of the invention.
[0027] Furthermore, the solid content of the modified para-aramid polymer solution is 2%-6%, the logarithmic viscosity at 30° C. with concentrated sulfuric acid as the solvent is 2.0-3.0 dL / g, and the dynamic viscosity at 25° C. is 200-600P.
[0028] The invention also discloses an application of a block copolymer modified para-aramid polymer solution, wherein the para-aramid polymer solution is applied in an aramid coated lithium battery separator.
[0029] The beneficial effects of the present invention are:
[0030] In the preparation method described in the present invention, a flexible third monomer is introduced into the para-aramid molecular chain that originally presents a rigid structure, thereby destroying the regularity of the traditional para-aramid, weakening the hydrogen bonding effect and crystallization ability between molecules, making it easy for solvent molecules to diffuse into the macromolecular chain, improving the solubility of the polymer, preventing the copolymer from precipitating from the solvent, avoiding the rigidity problem caused by the high molecular weight of para-aramid, and allowing the para-aramid polymer to be used in the field of diaphragm coating.
[0031] In the preparation method of the present invention, the performance of the polymer is adjusted by changing the molecular sequence structure of the polymer. The PPTA segment in the random copolymerization system has high rigidity and strong molecular chain interaction force, which affects the movement of the segment and the formation of the end group and is not conducive to chain extension. When the third monomer is first added to form an oligomer prepolymer for prepolymerization with terephthaloyl chloride and then the PPTA segment is grafted to form a block copolymer, due to the covalent action between different molecular chains, phase separation on a macroscopic scale is prevented, the hydrogen bond interaction force between the prepolymer and the PPTA segment is reduced, the solubility of the molecular chain in the later stage of the reaction and the movement ability of the segment in the system can be effectively improved, the orderliness of the molecular chain is reduced, and it is easy to control, so that a polymer solution with good flow performance, moderate molecular weight and stable performance can be obtained.
[0032] In the preparation method described in the present invention, the phenyl substitution of the third monomer and the presence of the ether bond allow a twisted structure to be formed in the molecular chain, which can form a straight chain structure under the action of temperature and tension. Due to the presence of the PPTA molecular chain segment, the thermal decomposition temperature of the modified para-aramid can reach above 500°C, which is conducive to obtaining a lithium battery separator with a high film rupture temperature, high puncture strength and excellent heat shrinkage performance.
[0033] In the preparation method and application of the present invention, the preparation method of the modified para-aramid copolymer stock solution is simple and feasible, the viscosity is adjustable, the fluidity is good and it is easy to coat and form a film, the process flow is simple, the production efficiency is high, and it is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A process flow chart for preparing modified aramid polymer solution and diaphragm;
[0035] Figure 2 This is the microscopic morphology of the aramid-coated lithium battery separator of Application Example 1. DETAILED DESCRIPTION
[0036] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0038] A method for preparing a block copolymer modified para-aramid polymer solution, the preparation method comprising:
[0039] S1. Preparation of polymerization solution:
[0040] Under an inert gas atmosphere, dissolving a solubilizing salt in an organic solvent to obtain the polymerization solution;
[0041] S2, precondensation:
[0042] A third monomer and terephthaloyl chloride are added to the polymerization solution, and the reaction temperature is controlled to perform a pre-polycondensation reaction to obtain an amino-terminated oligomer system, wherein the third monomer is any one of 3,4'-diaminodiphenyl ether (3,4'-ODA), 4,4'-diaminodiphenyl ether (4,4'-ODA), 1,3-bis(4-aminophenoxy)benzene (TPR-E), 4,4'-diaminobiphenyl (DABP), and 4,4'-diaminodiphenylmethane (MDA);
[0043] S3, block copolymerization:
[0044] Adding p-phenylenediamine and terephthaloyl chloride to the oligomer system, and controlling the stirring reaction temperature to carry out block copolymerization reaction under stirring conditions;
[0045] S4, Neutralization treatment:
[0046] After the block copolymerization reaction is completed, a neutralizing agent is added to neutralize the acidic substances generated during the reaction, and finally a modified para-aramid polymerization solution in a neutral environment is obtained.
[0047] Specifically, the organic solvent is at least one of N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N,N'-dimethylacetamide (DMAC), N,N'-dimethylacetamide (DMF), and 1,2-dimethyl-2-imidazolidinone (DMI);
[0048] The water content of the organic solvent is lower than 150 ppm, because terephthaloyl chloride reacts easily with water to form carboxylic acid, which reduces the reaction activity of the polymerization monomer.
[0049] Specifically, the dissolving salt is any one of calcium chloride and lithium chloride, and the mass concentration of the dissolving salt in the polymerization solution is 0.5% to 6%. When the concentration is too high, the thermal decomposition temperature of the polymer will be reduced, and when the concentration is too low, it will be unfavorable to increase the molecular weight of the polymer.
[0050] Specifically, in step S2, the molar ratio of the third monomer to terephthaloyl chloride is (1.05-1.2):1;
[0051] In step S3, the molar ratio of p-phenylenediamine to terephthaloyl chloride is (0.75-0.9):1;
[0052] The feeding amount of terephthaloyl chloride in step S2 accounts for 55% to 65% of the total feeding amount of terephthaloyl chloride in steps S2 and S3.
[0053] Specifically, the reaction temperature of step S2 is -5°C to 10°C; the reaction temperature of step S3 is -5°C to 10°C.
[0054] Preferably, the reaction temperature of step S2 is 0° C. to 5° C.; the reaction temperature of step S3 is -0° C. to 5° C. When the reaction temperature is low, it is not conducive to the full reaction of aromatic amine and terephthaloyl chloride. When the reaction temperature is high, terephthaloyl chloride releases a large amount of reaction heat, resulting in an increase in side reactions, affecting the normal progress of the polycondensation reaction.
[0055] Specifically, in step S4, the neutralizing agent is any one of calcium oxide, calcium hydroxide, calcium carbonate, lithium carbonate, and lithium hydroxide.
[0056] Specifically, in step S1, the temperature condition for preparing the polymerization solution is 60°C to 120°C;
[0057] In step S4, the temperature condition of the neutralization treatment is 70-100°C.
[0058] A block copolymer modified para-aramid polymer solution, wherein the modified para-aramid polymer solution is prepared according to the preparation method of the present invention.
[0059] Specifically, the solid content of the modified para-aramid polymer solution is 2%-6%, the inherent viscosity is 2.0-3.0 dL / g at 30° C. with concentrated sulfuric acid as solvent, and the dynamic viscosity is 200-600P at 25° C.
[0060] An application of a block copolymer modified para-aramid polymer solution, wherein the para-aramid polymer solution is used in an aramid coated lithium battery separator. The process flow for preparing the modified aramid polymer solution and the separator is as follows: Figure 1 shown.
[0061] 1. Example of Preparation of Para-aramid Polymerization Solution
[0062] Example 1
[0063] Preparation of a block copolymer modified para-aramid polymer solution:
[0064] (1) Add 400 mL of NMP to a 500 mL three-necked flask that has been dried and dehydrated, introduce dry nitrogen to ensure that the polymerization system is free of water and oxygen, add 5.17 g of calcium chloride to the system, heat the solution to 100 °C and stir until it dissolves.
[0065] (2) After the solubilizing salt is completely dissolved, the temperature is adjusted to room temperature, and 5.61 g (0.028 mol) of 3,4'-ODA is added to the system. After it is dissolved, 5.28 g (0.026 mol) of TPC is added. At this time, the temperature of the system is lowered to -5°C. After reacting for 30 minutes, an amino-terminated oligomer is obtained.
[0066] (3) Subsequently, 1.51 g (0.014 mol) of PPD and 3.41 g (0.0168 mol) of TPC were added, the agitator speed was increased, and the mixture was reacted at low temperature (-5°C) for 30 minutes to obtain a viscous liquid with fluidity.
[0067] (4) Stop the cooling medium and wait for the temperature to return to room temperature. Set the heating to 80°C. After the temperature reaches the target temperature, add calcium hydroxide to neutralize the hydrogen chloride produced during the reaction.
[0068] The block copolymer modified para-aramid polymer prepared by the above method has a solid content of 3.6%, a logarithmic viscosity of 2.35 dL / g, and a dynamic viscosity of 260P.
[0069] Example 2
[0070] Preparation of a block copolymer modified para-aramid polymer solution:
[0071] (1) Add 400 mL of DMAC to a 500 mL three-necked flask that has been dried and dehydrated, introduce dry nitrogen to ensure that the polymerization system is free of water and oxygen, add 11.59 g of lithium chloride to the system, heat the solution to 80°C and stir until it dissolves.
[0072] (2) After the solubilizing salt is completely dissolved, the temperature is adjusted to room temperature, and 3.60 g (0.018 mol) of 4,4'-ODA is added to the system. After it is dissolved, 3.45 g (0.017 mol) of TPC is added. At this time, the temperature of the system is lowered to 8°C. After reacting for 20 minutes, an amino-terminated oligomer is obtained.
[0073] (3) Subsequently, 1.24 g (0.0115 mol) of PPD and 2.64 g (0.013 mol) of TPC were added, the agitator speed was increased, and the mixture was reacted at low temperature for 30 minutes to obtain a viscous liquid with fluidity.
[0074] (4) Stop the cooling medium and wait for the temperature to return to room temperature. Set the heating to 90°C. After the temperature reaches the target temperature, add lithium carbonate to neutralize the hydrogen chloride produced during the reaction.
[0075] The block copolymer modified para-aramid polymer prepared by the above method has a solid content of 2.5%, a logarithmic viscosity of 2.90 dL / g, and a dynamic viscosity of 465P.
[0076] Example 3
[0077] Preparation of a block copolymer modified para-aramid polymer solution:
[0078] (1) Add 400 mL of DMI to a 500 mL three-necked flask that has been dried and dehydrated, introduce dry nitrogen to ensure that the polymerization system is free of water and oxygen, add 21.64 g of calcium chloride to the system, heat the solution to 120 °C and stir until it dissolves.
[0079] (2) After the solubilizing salt is completely dissolved, the temperature is adjusted to room temperature, and 7.31 g (0.026 mol) of TPE-R is added to the system. After it is dissolved, 4.84 g (0.024 mol) of TPC is added. At this time, the temperature of the system is lowered to 4°C. After reacting for 30 minutes, an amino-terminated oligomer is obtained.
[0080] (3) Subsequently, 2.08 g (0.0192 mol) of PPD and 4.26 g (0.021 mol) of TPC were added, the agitator speed was increased, and the mixture was reacted at low temperature for 60 minutes to obtain a viscous liquid with fluidity.
[0081] (4) Stop the cooling medium and wait for the temperature to return to room temperature. Set the heating to 100°C. After the temperature reaches the target temperature, add calcium carbonate to neutralize the hydrogen chloride produced during the reaction.
[0082] The block copolymer modified para-aramid polymer prepared by the above method has a solid content of 4.1%, a logarithmic viscosity of 2.76 dL / g, and a dynamic viscosity of 364P.
[0083] Example 4
[0084] Preparation of a block copolymer modified para-aramid polymer solution:
[0085] (1) Add 400 mL of DMF to a 500 mL three-necked flask that has been dried and dehydrated, introduce dry nitrogen to ensure that the polymerization system is free of water and oxygen, add 11.73 g of lithium chloride to the system, heat the solution to 90°C and stir until it dissolves.
[0086] (2) After the solubilizing salt is completely dissolved, the temperature is adjusted to room temperature, and 3.68 g (0.020 mol) of DABP is added to the system. After it is dissolved, 4.67 g (0.022 mol) of TPC is added. At this time, the temperature of the system is lowered to 10°C. After reacting for 20 minutes, amino-terminated oligomers are obtained.
[0087] (3) Subsequently, 1.80 g (0.018 mol) of PPD and 4.06 g (0.020 mol) of TPC were added, the agitator speed was increased, and the mixture was reacted at low temperature for 40 minutes to obtain a viscous liquid with fluidity.
[0088] (4) Stop the cooling medium and wait for the temperature to return to room temperature. Set the heating to 70°C. After the temperature reaches the target temperature, add lithium hydroxide to neutralize the hydrogen chloride produced during the reaction.
[0089] The block copolymer modified para-aramid polymer prepared by the above method has a solid content of 3.8%, a logarithmic viscosity of 2.15 dL / g, and a dynamic viscosity of 219P.
[0090] Example 5
[0091] The block copolymer modified para-aramid polymer solution was prepared by the method of Example 1, except that the third monomer added in step (2) was MDA.
[0092] The obtained block copolymer modified para-aramid polymer liquid has a solid content of 3.6%, a logarithmic viscosity of 2.60 dL / g, and a dynamic viscosity of 408P.
[0093] Example 6
[0094] The block copolymer modified para-aramid polymer solution was prepared by the method of Example 1, except that the polymerization reaction temperature in step (2) and step (3) was 0°C.
[0095] The obtained block copolymer modified para-aramid polymer liquid has a solid content of 3.6%, a logarithmic viscosity of 2.68 dL / g, and a dynamic viscosity of 238P.
[0096] Example 7
[0097] The block copolymer modified para-aramid polymer solution was prepared by the method of Example 2, except that the polymerization reaction temperature in step (2) and step (3) was 2°C.
[0098] The obtained block copolymer modified para-aramid polymer liquid has a solid content of 2.5%, a logarithmic viscosity of 2.98 dL / g, and a dynamic viscosity of 372P.
[0099] Comparative Example 1
[0100] The para-aramid polymer solution was prepared by the same method as in Example 1, except that no third monomer was added in this comparative example 1. The specific preparation process is as follows:
[0101] (1) Add 400 mL of NMP to a 500 mL three-necked flask that has been dried and dehydrated, introduce dry nitrogen to ensure that the polymerization system is free of water and oxygen, add 5.17 g of calcium chloride to the system, heat the solution to 100 °C and stir until it dissolves.
[0102] (2) After the solubilizing salt is completely dissolved, the temperature is adjusted to room temperature, and 4.86 (0.045 mol) PPD is added to the system. After dissolution, the system temperature is lowered to -5°C, and 9.44 g (0.0465 mol) TPC is added. The agitator speed is increased. After reacting at low temperature for 10 minutes, the system phases are separated and solids are precipitated.
[0103] The solid content of the para-aramid prepared by the above method is 3.2%, the logarithmic viscosity is 5.25 dL / g, and the dynamic viscosity cannot be measured.
[0104] Comparative Example 2
[0105] The para-aramid polymer solution was prepared by the same method as in Example 1, except that the pre-polycondensation and block copolymerization reactions were carried out simultaneously in this comparative example 2. The specific preparation process is as follows:
[0106] (1) Add 400 mL of NMP to a 500 mL three-necked flask that has been dried and dehydrated, introduce dry nitrogen to ensure that the polymerization system is free of water and oxygen, add 5.17 g of calcium chloride to the system, heat the solution to 100 °C and stir until it dissolves.
[0107] (2) After the solubilizing salt is completely dissolved, the temperature is adjusted to room temperature, and 1.51 g (0.014 mol) of PPD and 5.28 g (0.026 mol) of 3,4'-ODA are added to the system. After they are completely dissolved, the system temperature is lowered to -5°C, and 8.69 g (0.0428 mol) of TPC is added in three portions within 30 minutes. After reacting for 60 minutes, a viscous liquid is obtained.
[0108] (3) Stop the cooling medium, set the heating to 90°C, and add calcium hydroxide to neutralize the hydrogen chloride produced during the reaction.
[0109] The modified para-aramid polymer liquid prepared by the above method has a solid content of 3.6%, a logarithmic viscosity of 3.52 dL / g, and a dynamic viscosity of 649P.
[0110] Comparative Example 3
[0111] The para-aramid polymer solution was prepared by the same method as in Comparative Example 2, except that in Comparative Example 3, terephthaloyl chloride was added into the reaction system at one time.
[0112] The modified para-aramid polymer liquid prepared by the above method has a solid content of 3.6%, a logarithmic viscosity of 1.98 dL / g, and a dynamic viscosity of 192P.
[0113] Comparative Example 4
[0114] The para-aramid polymer solution was prepared by the same method as in Example 1, except that the amount of the third monomer was increased in this comparative example 4. The specific preparation process is as follows:
[0115] (1) Add 400 mL of NMP to a 500 mL three-necked flask that has been dried and dehydrated, introduce dry nitrogen to ensure that the polymerization system is free of water and oxygen, add 5.17 g of calcium chloride to the system, heat the solution to 100 °C and stir until it dissolves.
[0116] (2) After the solubilizing salt is completely dissolved, the temperature is adjusted to room temperature, and 7.81 g (0.039 mol) of 3,4'-ODA is added to the system. After it is dissolved, 5.28 g (0.026 mol) of TPC is added. At this time, the temperature of the system is lowered to -5°C. After reacting for 30 minutes, an amino-terminated oligomer is obtained.
[0117] (3) Subsequently, 1.51 g (0.014 mol) of PPD and 3.41 g (0.0168 mol) of TPC were added, the agitator speed was increased, and the mixture was reacted at low temperature (-5°C) for 30 minutes to obtain a viscous liquid with fluidity.
[0118] (4) Stop the cooling medium and wait for the temperature to return to room temperature. Set the heating to 80°C. After the temperature reaches the target temperature, add calcium hydroxide to neutralize the hydrogen chloride produced during the reaction.
[0119] The block copolymer modified para-aramid polymer prepared by the above method has a solid content of 3.4%, a logarithmic viscosity of 2.02, and a dynamic viscosity of 233P.
[0120] The inherent viscosity and dynamic viscosity performance results of the para-aramid polymer solutions in the above Examples 1-7 and Comparative Examples 1-4 are shown in Table 1 below.
[0121] The detection method of the logarithmic viscosity is as follows: after the polymer solution is washed and dried, a 0.5 dL / g concentrated sulfuric acid (mass fraction 98%) solution is prepared, and an Ubbelohde viscometer with a capillary inner diameter of 1.07 mm is used to test the outflow time of the solvent and the solution at 30°C. The calculation formula is: .in, t is the time it takes for the solution to flow out of the Ubbelohde viscometer, t 0 is the time it takes for concentrated sulfuric acid to flow out of the Ubbelohde viscometer, c It is the number of grams of polymer in 100 mL of solvent.
[0122] Table 1 Performance results of the polymer solutions of Examples 1-7 and Comparative Examples 1-4
[0123]
[0124] From the data in Table 1 above, it can be seen that the modified para-aramid block copolymers prepared by the method of the present invention in Examples 1-7 have more stable logarithmic viscosity and dynamic viscosity indicators, and are suitable for adapting the diaphragm coating process to obtain lithium battery coated diaphragms with excellent performance. The present invention introduces flexible segments into the PPTA rigid segments in a regular manner through block copolymerization, regulates the molecular structure, improves the solubility and fluidity of the copolymer, and achieves precise control of the copolymer. The production process of the polymerization liquid is simple, the performance indicators are stable, and it is easy to be applied to the field of diaphragm coating to obtain a lithium battery diaphragm with good heat shrinkage performance, high puncture strength, and high film rupture temperature.
[0125] From the data of comparative example 1, it can be seen that when the third monomer is not added for copolymerization, the low-temperature polycondensation of p-phenylenediamine and terephthaloyl chloride will directly separate into phases. At this time, PPTA has a purely rigid structure and can only be dissolved in strong acids such as concentrated sulfuric acid. It has poor solubility and cannot be used in the field of diaphragm coating.
[0126] It can be seen from the data of Comparative Example 2 that when the three monomers are randomly copolymerized, the obtained polymer has a larger logarithmic viscosity, that is, a higher molecular weight and a higher dynamic viscosity. It needs to be diluted for coating application, which makes the application process complicated and can easily cause poor diaphragm performance.
[0127] It can be seen from the data of Comparative Example 3 that the addition of terephthaloyl chloride once will cause a violent reaction in the initial stage of the polymerization, releasing a large amount of reaction heat, and increasing the side reactions of terephthaloyl chloride, which is not conducive to the subsequent polymerization reaction, resulting in a poor degree of polymerization, poor logarithmic viscosity and dynamic viscosity data, which will affect the corresponding performance indicators when applied to lithium battery separators.
[0128] It can be seen from the data of Comparative Example 4 that if the amount of the third monomer added is too much, the content of p-phenylenediamine that provides a rigid structure in the corresponding polymerization reaction will be reduced, which will lead to a slightly lower logarithmic viscosity, affecting the molecular weight and degree of polymerization of the polymer solution, and affecting the mechanical properties such as the puncture strength of the lithium battery separator.
[0129] 2. Application examples of polymer liquid in lithium battery separator
[0130] The copolymers prepared in Examples 1-7 and Comparative Examples 1-4 are applied to the field of lithium battery separators, corresponding to Application Examples 1-7 and Application Comparative Examples 1-4, respectively. The specific coating process is:
[0131] After filtering and degassing the modified para-aramid polymer solution, a coating machine is used to evenly coat the polymer solution on a 9-micron thick PE base film. After coagulation, water washing and drying, an aramid coated diaphragm is obtained, wherein the coagulation bath is a mixed solution of NMP and water, the mass concentration of NMP is 20%, and the solution temperature is 25°C.
[0132] The microscopic morphology of the diaphragm prepared in Application Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the coated diaphragm obtained by using the modified para-aramid copolymer has dense and uniform pores and contains a rich porous structure, which is conducive to the penetration of the electrolyte, improves the ion transmission capacity, and ensures excellent electrochemical performance.
[0133] The performance tests of the diaphragms prepared in Application Examples 1-7 and Comparative Examples 1-4 are performed. The specific test results are shown in Table 2 below, where the testing methods involved are: the diaphragm thickness, thermal shrinkage rate, and puncture strength testing standards are GB / T 36363-2018, and the film rupture temperature testing standard is GB / T36800.1-2018.
[0134] Table 2 Performance test results of polymer solution applied to lithium battery separator
[0135]
[0136] It can be seen from the data in Table 2 above that the lithium battery diaphragms prepared by the modified para-aramid polymer solution of Application Examples 1-7 have excellent performance, and their heat shrinkage performance, puncture strength, membrane rupture temperature and other indicators are better than those of random copolymers, which can further improve the safety performance of lithium battery diaphragms and enable them to be better applied in the lithium battery industry.
[0137] From the comparative example 1, it can be seen that if the third monomer is not introduced for copolymerization, the para-aramid fiber has high rigidity and will separate into phases during polymerization, and thus cannot form a film to prepare a coated diaphragm.
[0138] From the data comparison between Application Example 1 and Application Comparative Example 2, it can be seen that if the block copolymerization method is not adopted, the obtained polymer is used to prepare the lithium battery separator using the same coating process, and its heat shrinkage performance and film rupture temperature are significantly reduced. Therefore, the modified para-aramid polymer solution prepared by the preparation method of the present invention is beneficial to improving the heat resistance and safety performance of lithium batteries.
[0139] It can be seen from the comparative example 3 that the one-time feeding of terephthaloyl chloride will affect the polymerization effect, resulting in poor performance indicators of the diaphragm.
[0140] From the comparison of the data of Application Comparative Example 4 and Example 1, it can be seen that if the amount of the third monomer added is large, the increase of the molecular weight in the polymerization process is affected, resulting in the mechanical properties of the diaphragm being affected.
[0141] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0142] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. An application of a block copolymer modified para-aramid polymer solution, characterized in that: Modified para-aramid polymer solution is used in aramid-coated lithium battery separators; The preparation method of the modified para-aramid polymer solution is: S1. Preparation of polymerization solution: Under an inert gas atmosphere, dissolving a solubilizing salt in an organic solvent to obtain the polymerization solution; S2, precondensation: Adding a third monomer and terephthaloyl chloride to the polymerization solution, controlling the reaction temperature to perform a pre-polycondensation reaction, and obtaining an amino-terminated oligomer system, wherein the third monomer is any one of 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 4,4'-diaminobiphenyl, and 4,4'-diaminodiphenylmethane; S3, block copolymerization: Adding p-phenylenediamine and terephthaloyl chloride to the oligomer system, and controlling the stirring reaction temperature to carry out block copolymerization reaction under stirring conditions; S4, Neutralization treatment: After the block copolymerization reaction is completed, a neutralizing agent is added to neutralize the acidic substances generated during the reaction, and finally a modified para-aramid polymerization liquid in a neutral environment is obtained; In step S2, the molar ratio of the third monomer to terephthaloyl chloride is (1.05-1.2):1; In step S3, the molar ratio of p-phenylenediamine to terephthaloyl chloride is (0.75-0.9):1; The amount of terephthaloyl chloride charged in step S2 accounts for 55% to 65% of the total amount of terephthaloyl chloride charged in steps S2 and S3; In step S4, the neutralizing agent is any one of calcium oxide, calcium hydroxide, calcium carbonate, lithium carbonate, and lithium hydroxide; The solid content of the modified para-aramid polymer solution is 2% to 6%.
2. The use of a block copolymer modified para-aramid polymer solution according to claim 1, characterized in that: The organic solvent is at least one of N-methylpyrrolidone, N-ethylpyrrolidone, N,N'-dimethylacetamide, N,N'-dimethylacetamide, and 1,2-dimethyl-2-imidazolidinone; The water content of the organic solvent is lower than 150 ppm.
3. The use of a block copolymer modified para-aramid polymer solution according to claim 1, characterized in that: The dissolution-aiding salt is any one of calcium chloride and lithium chloride, and the mass concentration of the dissolution-aiding salt in the polymerization solution is 0.5% to 6%.
4. The use of a block copolymer modified para-aramid polymer solution according to claim 1, characterized in that: The reaction temperature of step S2 is -5°C to 10°C; the reaction temperature of step S3 is -5°C to 10°C.
5. The use of a block copolymer modified para-aramid polymer solution according to claim 1, characterized in that: In step S1, the temperature condition for preparing the polymerization solution is 60°C to 120°C; In step S4, the temperature condition of the neutralization treatment is 70-100°C.
6. The use of a block copolymer modified para-aramid polymer solution according to claim 1, characterized in that: The modified para-aramid polymer solution has a logarithmic viscosity of 2.0-3.0 dL / g at 30° C. using concentrated sulfuric acid as a solvent, and a dynamic viscosity of 200-600 P at 25° C.
Citation Information
Patent Citations
Aramid coated lithium ion battery diaphragm and preparation method thereof
CN104993089A
High-temperature-resistant aramid fiber lithium ion battery composite separation membrane and preparation method thereof
CN107170942A
Preparation method of para-aramid lithium ion battery diaphragm
CN110729437A